Dynamic Regulation of Single-Stranded Telomeres in Saccharomyces cerevisiae - Smith, Stephanie (Genetics Society of America, 2008)
The temperature-sensitive phenotypes of yku70Δ and yku80Δ have provided a useful tool for understanding telomere homeostasis. Mutating the helicase domain of the telomerase inhibitor Pif1 resulted in the inactivation of cell cycle checkpoints and the subsequent rescue of temperature sensitivity of the yku70Δ strain. The inactivation of Pif1 in yku70Δ increased overall telomere length. However, the long G-rich, single-stranded overhangs at the telomeres, which are the major cause of temperature sensitivity, were slightly increased. Interestingly, the rescue of temperature sensitivity in strains having both pif1-m2 and yku70Δ mutations depended on the homologous recombination pathway. Furthermore, the BLM/WRN helicase yeast homolog Sgs1 exacerbated the temperature sensitivity of the yku70Δ strain. Therefore, the yKu70-80 heterodimer and telomerase maintain telomere size, and the helicase activity of Pif1 likely also helps to balance the overall size of telomeres and G-rich, single-stranded overhangs in wild-type cells by regulating telomere protein homeostasis. However, the absence of yKu70 may provide other proteins such as those involved in homologous recombination, Sgs1, or Pif1 additional access to G-rich, single-stranded DNA and may determine telomere size, cell cycle checkpoint activation, and, ultimately, temperature sensitivity.